Benefits of emotional integration and costs of emotional distancing. Issue 6 (5th February 2018) - Roth, Guy; Shahar, Bat‐Hen; Zohar‐Shefer, Yael; Benita, Moti; Moed, Anat; Bibi, Uri; Kanat‐Maymon, Yaniv; Ryan, Richard M.
Abstract: Objective: Three studies explored the consequences of the self‐determination theory conception of integrative emotion regulation (IER; Ryan & Deci, 2017), which involves an interested stance toward emotions. Emotional, physiological, and cognitive consequences of IER were compared to the consequences of emotional distancing (ED), in relation to a fear‐eliciting film. Method: In Study 1, we manipulated emotion regulation by prompting students' ( N  = 90) IER and ED and also included a control group. Then we tested groups' defensive versus nondefensive emotional processing, coded from post‐film written texts. Study 2 ( N  = 90) and Study 3 ( N  = 135) used the same emotion regulation manipulations but exposed participants to the fear‐eliciting film twice, 72 hr apart, to examine each style's protection from adverse emotional, physiological, and cognitive costs at second exposure. Results: Participants who had been prompted to practice IER were expected to benefit more than participants in the ED and control groups at second exposure, as manifested in lower arousal and better cognitive capacity. Overall, results supported our hypotheses. Conclusions: The current studies provide some support for the assumption that in comparison to ED, taking interest in and accepting one's negative emotions are linked with less defensive processing of negative experiences and with better functioning.